Three-dimensional visualisation of spatially dispersed phenomena on the example of the Eduroam wireless network signal analysis in the university building - Górniak, Grzegorz; Kunz, Mieczysław (Quaestiones Geographicae, 2025)
The study describes the procedure and conditions for performing geovisualisations based on dispersed measurement data obtained at specified spatial intervals. The research utilised a rarely used method of representing dispersed phenomena in the form of static three-dimensional visualisation. The work presents the procedure necessary to create a clear and cartographically effective image of a phenomenon that is not directly observable but recorded using specialised equipment. The method was tested by analysing the spatial distribution and intensity of the signal strength of the Eduroam wireless access system operating in the building of the Faculty of Earth Sciences and Spatial Management at Nicolaus Copernicus University in Toruń. The outcome is a three-dimensional model of the signal distribution of this network within selected size intervals. The results support the building administrator’s decision-making processes regarding the optimal placement of internal access points. Geographic information system (GIS) software and raster applications for processing and integrating image data were used in the conducted activities. The methodological part describes data acquisition, geodatabase creation, statistical analysis, and data interpolation using spline functions and surface estimation. The development of 3D GIS tools not only enables more precise analyses but also contributes to a better understanding of the distribution of non-linearly dispersed phenomena in space. The presented method and the results of the conducted research contribute to the practical application development of 3D GIS systems.